Strangers and neighbors : multiculturalism, conflict, and community in America - Voyer, Andrea M., 1972- (Cambridge : Cambridge University Press, 2013)
In Strangers and Neighbors, Andrea M. Voyer shares five years of observations in the city of Lewiston. She shows how long-time city residents and immigrant newcomers worked to develop an understanding of the inclusive and caring community in which they could all take part. Yet the sense of community developed in Lewiston was built on the appreciation of diversity in the abstract rather than by fostering close and caring relationships across the boundaries of class, race, culture, and religion. Through her sensitive depictions of the experiences of Somalis, Lewiston city leadership, anti-racism activists, and even racists, Voyer reveals both the promise of and the obstacles to achieving community in the face of diversity.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Somalis -- Maine -- Lewiston -- Social conditions; Immigrants -- Maine -- Lewiston -- Social conditions; Multiculturalism -- Maine -- Lewiston; Community development -- Maine -- Lewiston; Lewiston (Me.) -- Race relations; Lewiston (Me.) -- Social conditions -- 21st century